Efeito das variáveis climáticas nas características do sêmen, testosterona e cortisol em bovinos - Mizusaki, Kristoffer Toshiyuki (2011)
The objective of this work was to study the seasons influence (spring, summer, autumn and winter) on semen characteristics and hormones (testosterone and cortisol) in Nelore and Simental bulls. Five Nelore and five Simental bulls were 48-72 months old, extensively managed, were evaluated for sexual soundness using physical and morphological characteristics of semen and hormonal serum levels. There was decreased motility and vigor semen (P<0.05) during winter in Simental bulls. There was correlation between serum testosterone and cortisol (P<0.01) to motility and vigor in either Nelore and Simental bulls. In conclusion, these results showed a hormonal and semen characteristics variation throughout the season change the semen quality. Bulls from Nelore breed differed from Simental, demonstrating adaptability to the field conditions.